Performance and Emission Characteristics of Supercharged Biomass Producer Gas-Diesel Dual Fuel Engine - Mohd Nor, Mohd Faizairi (2010)

(untitled)
The performance and emission characteristics of supercharged producer gas-diesel dual fuel engine has been investigated and evaluated. In this study, producer gas which was generated from gasifier and intake air were injected separately and mixed at the engine’s intake manifold. Experiments were carried out at a constant injection pressure and flowrate of both producer gas and air. The performance and emission characteristics of dual fuel engine were investigated by supercharged producer gas-diesel dual fuel, premixed producer gas-diesel dual fuel and diesel fuel at constant engine speed and different loads. It was found that by supercharging the producer gas-diesel dual fuel mixture, the diesel fuel substitution and brake thermal efficiency were slightly increased and there is a reduction in carbon monoxide emission and specific energy consumption as compared to premixed producer gas-diesel dual fuel. The main reason is because relatively complete combustion occurred due to more air utilization which increase in engine volumetric efficiency under these conditions. Therefore, the experimental results indicate that the supercharging is an effective way on improvement of combustion characteristics and at the same time a reduction of unburned gas emissions in dual fuel producer gas-diesel operation.